Hidden in Plain Sight: Insurrectionary Anarchism in the Anti-Government Extremism Landscape - Lubrano, Mauro (Perspectives on terrorism, 2024)
Anti-government extremism (AGE) stands as a significant contemporary manifestation of political violence. As such, recent scholarly publications have sought to provide novel conceptualisations and analyses of this phenomenon. Despite these valuable contributions, a prominent expression of anti-government extremism - insurrectionary anarchism - is largely absent from the scholarly debate. The aim of this article is thus to narrow this gap by providing a comprehensive exploration and overview of insurrectionary anarchism. To do so, this article builds on the definitions and frameworks elaborated in recent publications to demonstrate that insurrectionary anarchism can and should be included in the contemporary debate on anti-government extremism. Adopting a distinction between ideological and issue-driven anti-government extremism proposed in the literature, this analysis argues that, while insurrectionary anarchism’s fundamental opposition to any hierarchical power structures remains its underlying rationale and justification, it essentially functions as a phenomenon driven by specific issues. As part of a lively and varied milieu, insurrectionary anarchist AGE shares parallels with the broader spectrum of anti-government extremism, including an inclination for conspiracy thinking and systematic targeting of politicians and/or governmental representatives. Although it diverges in scale and operational methods from other expressions of AGE, insurrectionary anarchism continues to represent a complex phenomenon that also holds the potential for escalation.